Dry needling in the reduction of lumbar pain and functional disability: an integrating review - Nadalon, Natieli Rodrigues (2024)
The present study aims to review the scientific literature and identify, through scientific articles, the effect of dry needling in individuals with low back pain, highlighting the improvement in pain and functional disability. Through a search in the PubMed, Bireme, SciELO and PEDro databases, using the keywords “low back pain”, “lumbar pain”, “physical therapy”, as well as “low back pain” “low back pain” and “physiotherapy”. In studies published between 2014 and 2018. Six articles were included in this study, among which the majority showed that the application of dry needling brought some benefits in relation to pain and / or functional disability in patients who had low back pain. The results of the research demonstrated that individuals with low back pain, when submitted to treatment with dry needling at the myofascial trigger points, showed improvement in the pain and / or disability, presenting benefit from the first needling session.